Risk factors for Alzheimer disease: A population-based case-control study in Istanbul, Turkey - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
The objective is to study risk factors for Alzheimer disease (AD) in Istanbul, Turkey. This is a population-based case-control study. We screened people over age 70 in the community for cognitive impairment. The screen positives and a proportion of screen negatives underwent neurologic examination in the second phase. Cases were 57 probable AD patients and controls were 127 cognitively normal individuals identified by neurologic examination. Odds ratios (OR) were calculated using multivariate logistic regression analysis. Having a university/college degree had a protective effect on AD risk (OR = 0. 10 95% confidence interval [CI] = 0.02-0.50). Exposure to occupational electromagnetic field had an OR of 4.02 (95% CI = 1.02-15.78). Use of electricity for residential heating also showed elevated risk (OR = 2.77, 95% CI = 1.12-6.85). Our results suggest that having a higher education is protective from AD and that electromagnetic field exposure at work or at home is a significant risk factor.
Keywords: risk factors; education; electromagnetic field; EMF; Turkey; EURODEM POOLED ANALYSES; VASCULAR DEMENTIA; EDUCATION; PREVALENCE; EXPOSURE; HEALTH; CANADA; GENDER; AD; ASSOCIATION